"Application of a competence approach in the process of training future officers of the National Guard of Ukraine" - Mirshuk, O. (Problems of Engineer-Pedagogical Education, 2018)
The paper analyzes the main approaches of both domestic and foreign scholars to developing a competence approach as a higher education methodology for training future specialists and to defining the concept of a competence approach. Ways of applying a competence approach in the process of training civilian and military specialists are considered. A theoretical analysis of special competences necessary for carrying out professional activity while acquiring higher military education is conducted. Special emphasis is placed on the analysis of projects for higher education standards and some guidance documents that regulate the formation of competences of future officers at the tactical and operational-tactical level of the National Guard of Ukraine. The article highlights the necessity for further scientific research into ways of mastering the competences that will ensure successful professional activity. The problem of constructing solid competence models of graduates of higher military educational institutions is outlined.